(untitled) (Higher Education Politics and Economics, 2021)
While the popularity of state-financed merit-based scholarships has increased since the 1980s, policymakers struggle to maintain these programs because of growing costs. Some have tried to manage this tradeoff through eligibility changes or award amounts; however, little empirical research exists on the effectiveness of these changes. We add to the financial aid literature by determining if college enrollment responded to a 2013 restructuring of Arkansas’s Academic Challenge Scholarship from equal annual awards to a backloaded system with progressively higher payouts to students who persisted. We identify no statistically significant impacts associated with the 2013 change; however, point estimates are generally negative. We believe this is the first study to examine if moving to a backloaded payout structure affects college enrollment.